Perbandingan GreenKonstitusi, GreenEkonomi, dan Hukum Ekonomi Syariah di Indonesia - Yasin, Mohamad Nur (UIN Sunan Kalijaga, 2016)
The rejection of unjustice exploitation to natural environment is central theme of green constitution, green economic, and sharia economic law. The problems, how do comparison of essence and implementation between one and others. In this paper is used study method in law normative. There are two important findings. First, the similarity of essence of green constitution, greeneconomic, and sharia economic law is focus on environment justice (eco-justice). The differences, environment justice under perspective of (a) green constitution means natural environment has to be welfare of people, (b) green economic means natural environment is part of production, distribution, and ethical consumption, and (c) sharia economic law means give the right for future generations to enjoy natural environment. Second, the similarity of implementation challenge faced by three concepts is inconsistention of law. The differences, inconsistention of law faced by (a) green constitution isinconsistension of environments Act with 1945 Constitution, (b) green economic is the loss of unlawfull meaning of lawful term (c) sharia economic law is systemic disobedience by sharia corporation to sharia principles.